PEMILIHAN LANSIA DALAM PEMBAGIAN PERAN DOMESTIK BAGI KELUARGA KARIR DI KECAMATAN SAGULUNG KOTA BATAM - Celline Deon, Ruth (Regalia: Jurnal Riset Gender dan Anak, 2022)
This study aims to determine the selection of the elderly in the division of domestic roles for career families in Sagulung District, Batam City. This type of research is a qualitative descriptive research type. Data collection techniques using observation and in-depth interviews. The sampling technique used purposive sampling method. The data analysis technique used qualitative. The results show that the division of domestic roles for career families includes caring for grandchildren and doing household chores, with the following reasons: the elderly worry if their grandchildren are treated badly, worry if their grandchildren are closer to the maid than their parents, worry if the maid gives bad teachings and not polite, and the elderly are worried if all the needs of the grandchildren are done by the maid.